Arte Nuova and the Italian Auto Industry at Early 20th-Century Expositions - Clericuzio, Peter (Lo sguardo rinnovato, 2026)
The key moment of modernism in Italy, long cited as coinciding with the birth of Futurism in 1909, deserves to be reconsidered. A better date would be nearly a decade earlier, with the country’s introduction to Arte Nuova, also known as the Stile Liberty, the Italian strand of Art Nouveau. This phenomenon was made possible by Art Nouveau’s favored status at turn-of-the century international fairs, including the Turin Exposition of Modern Decorative Art in 1902, the moment when the national auto industry adopted it wholeheartedly. Arte Nuova was used by most Italian car manufacturers, led by FIAT, for the ephemeral architecture at major automobile shows for the rest of the decade, linking its rationalist structure with technological advancement, fine craftsmanship, and novelty to reach a broad public. Despite the fluctuating economic fortunes of the nascent industry, FIAT would carry Arte Nuova into the 1910s for its permanent architecture and prodigious advertising campaigns.